Terminal effects of optogenetic stimulation on dopamine dynamics in rat striatum - Bass, Caroline E. (2013)
In this study, the first in-depth analysis of optically induced dopamine release using fast-scan cyclic voltammetry on striatal slices from rat brain was performed. An adeno-associated virus that expresses Channelrhodopsin-2 was injected in the substantia nigra. Tissue was collected and sectioned into 400 μm-thick coronal slices four weeks later. Blue laser light (473 nm) was delivered through a fiber optic inserted into slice tissue. Experiments revealed some difference between maximal amplitudes measured from optically and electrically evoked dopamine effluxes. Specifically, there was an increase in the amplitude of dopamine release induced by electrical stimulation in comparison with light stimulations. However, we found that dopamine release is more sensitive to changes in the pulse width in the case of optical stimulation. Light-stimulated dopamine was increased as the stimulation pulse widened. There was no difference with repeated stimulations at five minute intervals between stimulation sources and dopamine signal was stable during recording sessions, while one minute intervals resulted in a decline in the amplitude from both sources. Optical stimulation can also produce an artifact that is distinguishable from dopamine by the cyclic voltammogram. These results confirm that optical stimulation of dopamine is a sound approach for future pharmacological studies in slices.